BRIC’S AFRICAN POLICY - Ahmet Yiğitalp Tulga (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2018)
In recent years, BRICS’ countries(Brazil, Russia, China, India and South Africa) have become Africa’s biggest economic partner. Across trade, investment, infrastructure, and aid, there is no other country with such depth and breadth of engagement in Africa. BRICS is a rising power and Africa is a continent that is still developing. There is evidence of an unequal parity of force, both financial and political, between the two areas in today’s worldwide connection. It will ask questions about BRICS’ diversions and strategies, and their suggestions towards the exchange agreements with African states. This study will examine the researchers conducted by African, Western and BRICS’ scholars. Their opinions will be considered objectively. From time to time, this study will compare the opinion of African, and western. This research will examine this association in comparison with Africa’s old colonial powers, and today enormous exchange inclusion with BRICS countries. This research aims to analyze the African’s view of BRICS’ African policy. The main question it to answer; Is BRICS best model for the development of Africa? This study analyses political and socio-economic advantages and disadvantages of BRICS’ Africa policy and relations between BRICS and African states. Nowadays, there are a lot of academic research about BRICS’ African policy. Some of these studies have focused on neo-colonialism. And some of them support BRICS’ African policy. However, a few studies care about African voice. The motivation of this research is to clarify African’s view about BRICS’ African policy and this thesis tries to show African’s opinion about BRICS policy and also, whether BRICS’ African policies are neo-colonialism or not.Keywords: BRICS, China, Russia, Brazil, Africa, African’s View, BRICS’ African Policy.